Exergy analysis of photovoltaic thermal (PVT) compound parabolic concentrator (CPC) for constant collection temperature mode. (October 2016) - Atheaya, Deepali; Tiwari, Arvind; Tiwari, G.N.
Highlights: The partially covered PVT-CPC collector system is investigated for the constant collection temperature mode. An overall exergy analysis of PVT-CPC system is carried out. Characteristic curve for fully covered PVT-CPC water collector for different constant collection temperatures is presented. Abstract: In this communication, an attempt has been made to evaluate exergy of photovoltaic thermal compound parabolic concentrator (PVT-CPC) water collector system [case (i)] for constant collection temperature mode of operation. The performance of PVT-CPC water collector systems can be analyzed in two modes namely (i) constant mass flow rate and (ii) constant collection temperature. In the present analysis, an analytical expression for mass flow rate and electrical efficiency of PV module for partially covered PVT-CPC water collector system [case (i)] have been developed to determined the performance under constant collection temperature mode. Such system will be most useful for thermal space heating of buildings to conserve fossil fuel to save environment. The comparison of proposed system with fully covered PVT-CPC water collectors [case (ii)], conventional CPC water collectors [case (iii)] and partially covered PVT water collectors [case (iv)] have also been carried out for climatic condition of New Delhi. Based on computation, it has been found that for fully covered PVT-CPC water collector system [case (ii)] (a) at high operating temperatures, instantaneous thermal efficiency has lower value in comparison with constant mass flow rate condition; (b) at high concentration ratio ( C  = 5), higher operating temperature is achieved. The analytical expression of the electrical efficiency of the proposed system is also derived. An overall thermal and exergy analysis of PVT-CPC water collector system in terms of energy degraded into the environment and exergy destruction have also been carried out.